Amenia Meeting - October 1877 (The American Institute of Mining, Metallurgical, and Petroleum Engineers, 1879)
The opening session was held on Tuesday evening, October 23d. Mr. J. F. Lewis, on behalf of the local committee of arrange ments, made a short address of greeting to the members assembled, and then introduced Gov. A. H. Holley, of Lakeville, Conn. Gov. Holley addressed the Institute as follows: Gentlemen, we give you cordial welcome to a mining, manufac turing, and agricultural country, of which we are not a little proud. We welcome you as an association, and as individuals. We invite you to an inspection of our resources, and to our methods of im proving them. We appreciate the results of your efforts in past years, and we anticipate good from your advice and counsel in the future. You are in the vicinity of some of the oldest mining and manufacturing operations in iron in our country. It will be our pleasure to conduct you to a mine which was worked for more than a half century before our country achieved national inde pendence, and to point out to you the spot where the products of this mine were wrought into cannon and shot during the progress of our Revolution. We can show you also a far larger area of mining country than was supposed to exist in this vicinity at that early day. There are, within a radius of thirty miles from this spot, ten mines at least that have been extensively worked, and there are as many more that have been occasionally worked, with a fair degree of success. All the mines that are wrought to any extent produce excellent qualities of iron, while many of them in various combinations produce as good material for the manufacture of steel, car wheels, axles, and many other purposes, as can be found in ally country. The old Salisbury iron retains its reputation for tensile strength unsurpassed, when made entirely from the ore of the old mine. The progress that has been made in the development of these mines since the days of the pickaxe, when the product was trans ported in pounds upon horseback, to those of the steam-engine, which now moves hundreds of tons per day, presents, indeed, a